The role of teachers in implementing the movement guidance program for students with physical disabilities in slb - Arhe Aan Yesa Purba; Annisa Amalia; Eko Lucky Setiawan; Kontesalonika br Sinulingga; Nabila Azzahra; Rizka Nurida Siregar (Indonesian Journal Education, 2026)
Students with physical disabilities experience limitations in their motor skills, which impact their daily activities and independence. This situation demands a planned and structured movement development program in Special Needs Schools (SLB). In its implementation, teachers play a crucial role not only as instructors but also as facilitators, guides, and evaluators in developing students' motor skills. This study aims to describe the role of teachers in implementing a movement development program for students with physical disabilities in SLB. The study used a qualitative approach with a descriptive method. Data collection techniques included observation, interviews, and documentation. The results indicate that the teachers' role in the movement development program includes program planning based on student needs assessments, gradual and continuous implementation of movement exercises, and evaluation of students' motor development and independence. Furthermore, the success of the movement development program is influenced by teacher competence, school environmental support, and parental involvement. Therefore, the teacher's role is a key factor in optimizing the implementation of the movement development program to improve the motor skills and independence of students with physical disabilities.